The mystery of Charles Dickens - Wilson, A. N., 1950- (Harper, an imprint of HarperCollinsPublishers, 2020)
Charles Dickens was a superb public performer, a great orator and one of the most famous of the Eminent Victorians. Slight of build, with a frenzied, hyper-energetic personality, Dickens looked much older than his fifty-eight years when he died<U+2015>an occasion marked by a crowded funeral at Westminster Abbey, despite his waking wishes for a small affair. Experiencing the worst and best of life during the Victorian Age, Dickens was not merely the conduit through whom some of the most beloved characters in literature came into the world. He was one of them. Filled with the twists, pathos, and unusual characters that sprang from this novelist<U+2019>s extraordinary imagination, The Mystery of Charles Dickens looks back from the legendary writer<U+2019>s death to recall the key events in his life. In doing so, he seeks to understand Dickens<U+2019> creative genius and enduring popularity. Following his life from cradle to grave, it becomes clear that Dickens<U+2019>s fiction drew from his life<U+2015>a fact he acknowledged. Like Oliver Twist, Dickens suffered a wretched childhood, then grew up to become not only a respectable gentleman but an artist of prodigious popularity. Dickens knew firsthand the poverty and pain his characters endured, including the scandal of a failed marriage. Going beyond standard narrative biography, A. N. Wilson brilliantly revisits the wellspring of Dickens<U+2019>s vast and wild imagination, to reveal at long last why his novels captured the hearts of nineteenth century readers<U+2015>and why they continue to resonate today.